Design and development of small and simple dual robot for inspecting pipe with perpendicular entry - Roslin N.S.; Anuar A.; Sahari K.S.M.; Bakar M.N.A.A. (Springer Verlag, 2023)
This paper presents the development of a small and simple dual robot system for pipe inspection activity. The objective is to propose small and simple dual robot in navigating perpendicular entry with sudden change in pipe diameter. Sudden change in diameter is referred to the drastic difference in size of the entry (80 mm in diameter) and the pipe (250 mm in diameter and above). The robot consists of two rectangular-shaped modules linked with a connector. The size of the body is 38 mm (width) × 55 mm (length) × 44 mm (height). Each module is driven by two micro metal gear motors. It uses caterpillar base for locomotion to provide larger surface contact to the pipe wall. The 2 degree-of-freedom (DoF) connector allows the robot to bend in pitch and yaw axes without any drive force required. Preliminary test result shows its ability to navigate through the expected geometry. © 2014 Springer Science+Business Media Singapore.